Acoustic field-assisted powder bed fusion of tungsten carbide-reinforced 316L stainless steel composites - Anfu Guo; Rongji Tang; Shuai Guo; Yingbin Hu; Xianliang Sheng; Yibao Zhang; Mingkang Zhang; Peng Qu; Shaoqing Wang (Journal of Materials Research and Technology, 2023)
Due to its excellent corrosion and oxidation resistance, good formability, and affordability, 316L stainless steel (SS) is widely used in industries such as biomedical, marine, chemical, and water treatment. However, to further enhance its mechanical properties, scholars have turned to reinforcing 316L SS with ceramic additives. Among ceramic additives, tungsten carbide (WC) is favored due to its good wettability ability to bond closely with iron-based materials. Despite these benefits, defects of cracks, pores, and balling commonly exist in WC-reinforced metal matrix composites due to the agglomeration of WC particles. In response to these problems, author propose a novel method that combines acoustic field (AF) with powder bed fusion (PBF) to process WC-reinforced 316L SS materials. This approach takes advantages of AF's ability to homogenize materials, smooth out thermal gradient, reduce cracks, and refine grains in liquid materials, while also utilizing PBF's capabilities to fabricate complex-shaped customized parts with high density and good quality. Experimental results have shown that adding an AF to the PBF can reduce dislocation density, mitigate stress, alleviate cracks, refine grain size, and alter grain shape, ultimately enhancing the tensile properties of WC-reinforced 316L SS composites. By adopting this method, a balance of strength and ductility can be achieved, with ultimate tensile strength and percentage elongation falling into a narrow but high range of 750–930 MPa and 44–55%, respectively.